Calapídeos do litoral brasileiro (Crustacea: Decapoda: Brachyura) - Sampaio, Célia Maria de Souza (1989)
This dissertation deals with all crustaceans species under the family CALAPPIDAE, occurring on the Brazilian coast. It consists of the following divisions: introduction, bibliographic revision, material and methods, results, conclusions and bibliographical references. The taxonomic section includes synonymy, diagnoses and keys for identification of each taxon below family. Besides characterization, data on coloration , size and origen of the materia1 examined, type-locality, known geographical distribution and considerations. All species are illustrated photographically (in dorsal, frontal and ventral views). The family CALAPPIDAE is represented in Brazil by two subfamilies, five genera and twelve species, which were grouped as for substrate habitat according to Coelho, Ramos-Porto & Koening criteria: one species occurs in mud, three occur both in fine sand and mud, four occur on hard bottom and four are euriedaphics. From twelve species studied, six had their known distribution area enriched with one or more localities of occurence. From these, only Hepatus scaber, known only from Northern Brazil was recorded for the first time at Rio de Janeiro shores (one specimen).